Does a decision aid for prostate cancer affect different aspects of decisional regret, assessed with new regret scales? A randomized, controlled trial. (3rd May 2015) - van Tol‐Geerdink, Julia J.; Leer, Jan Willem H.; Wijburg, Carl J.; van Oort, Inge M.; Vergunst, Henk; van Lin, Emile J.; Witjes, J. Alfred; Stalmeier, Peep F. M.
Abstract: Objective: To develop and validate new regret scales and examine whether a decision aid affects different aspects of regret in the treatment choice for prostate cancer. Methods: This was a multicentre trial (three sites) with imbalanced randomization (1 : 2). From 2008 to 2011, patients with localized prostate cancer were randomized 1 : 2 to usual care ( N  = 77) or usual care plus a decision aid presenting risks and benefits of different treatments ( N  = 163). The treatments were surgery and (external or interstitial) radiotherapy. Regret was assessed before, and 6 and 12 months after treatment, using the Decisional regret scale by Brehaut et al . ( Medical Decision Making, 23, 2003, 281), and three new scales focusing on process, option and outcome regret. The relation between decision aid and regret was analysed byanova . Results: The concurrent validity of the new regret scales was confirmed by correlations between regret and anxiety, depression, decision evaluation scales and health‐related quality of life. With a decision aid, patient participation was increased ( P  = 0.002), but regret was not. If anything, in patients with serious morbidity the decision aid resulted in a trend to less option regret and less Brehaut regret ( P  = 0.075 and P  = 0.061, with effect sizes of 0.35 and 0.38, respectively). Exploratory analyses suggest that high‐risk patients benefitted most from the decision aid. Conclusion: The new regret scales may be of value in distinguishing separate aspects of regret. In general, regret was not affected by the decision aid. In patients with serious morbidity, a trend to lower option regret with a decision aid was observed.